Master crack types and typical acoustic emission characteristics during rock failure - Zhao, Tongbin; Zhang, Pengfei; Xiao, Yaxun; Guo, Weiyao; Zhang, Yulong; Zhang, Xiufeng (International journal of coal science & technology, 2023)
Acoustic emission (AE) signals contain substantial information about the internal fracture characteristics of rocks and are useful for revealing the laws governing the release of energy stored therein. Reported here is the evolution of rock failure with different master crack types  as investigated using Brazilian splitting tests (BSTs), direct shear tests (DSTs), and uniaxial compression tests (UCTs). The AE parameters and typical modes of each fracture type were obtained, and the energy release characteristics of each fracture mechanism were discussed. From the observed changes in the AE parameters, the rock fracture process exhibits characteristics of staged intensification. The scale and energy level of crack activity in the BSTs were significantly lower than those in the DSTs and UCTs. The proportion of tensile cracks in the BSTs was 65%–75%, while the proportions of shear cracks in the DSTs and UCTs were 75%–85% and 70%–75%, respectively. During the rock loading process under different conditions, failure was accompanied by an increased number of shear cracks. The amplitude, duration, and rise time of the AE signal from rock failure were larger when the failure was dominated by shear cracks rather than tensile ones, and most of the medium- and high-energy signals had medium to low frequencies. After calculating the proposed energy amplitude ratio, the energy release of shear cracks was found to exceed that of tensile cracks at the same fracture scale.